A review of prospective Clinical Trials for neurogenic bladder: The place of surgery, experimental techniques and devices - Persu, Cristian; Braschi, Emmanuel; Lavelle, John (Central European journal of urology, 2014)
The neurogenic urinary bladder has been known for at least 30 years now and the concepts behind it are continuously evolving, but there is actually not much work that has been done to accumulate solid clinical evidence in this field. We review the surgical and experimental techniques used in the management of this condition. TO ACHIEVE OUR GOAL, WE PERFORMED INTERNET SEARCHES USING THE SAME SEARCH STRING: Urinary bladder, neurogenic. In each case, the search was limited to clinical trial, subjects were human and the language was English. After duplicate removal, we obtained a final number of 580 papers. Data was extracted from each paper into a database file and was analyzed separately for adult and pediatric populations. A total of 70 full text papers were reviewed and analyzed according to the previously mentioned algorithm. The first prospective, randomized surgical trials were published less than 20 years ago, starting with 1994, and the number of papers published each year since then has remained in the range of 1-3. The oldest prospective clinical trial for this indication dates back to 1975. The total number of patients included in surgical trials is 3453, out of which 59% are males. The papers include a total of 369 children (21.2%), essentially looking at all the techniques that are also used in adults. There is still a lot of work to be done in order to obtain a significant level of evidence in the field of surgical procedures used in neurogenic bladder patients.